ANALISIS PERBANDINGAN KUALITAS CUKO PEMPEK ASAM ASETAT DAN ASAM LAKTAT - Gunawan, Edi; Murtado, A.D.; Muchsiri, Mukhtarudin (Edible: Jurnal Penelitian Ilmu-ilmu Teknologi Pangan, 2013)
This research used a completely randomized design (CRD) arranged Factorially which consists of six units experiment were repeated three times with each unit experiment A1 (200 ml acetic acid), A2 (250 ml acetic acid), A3 (300 ml acetic acid), A4 (200 ml lactic acid), A5 (lactic acid 250 ml), and A6 (300 ml lactic acid). The parameters which observed in this research consists of acid total, acidity, sugar total, and viscosity. The organoleptic consists of color, flavour and taste. The results showed that the acetic concentration and lactic acid was veryÂ  significant effect to the acid total, acidity, sugar total and viscosity. The organoleptic test showed that the acetic acid comparation and lactic acid have significantly effect for color, flavor and taste of cuko pempek. The conclution from this research showed that A2 unit experiment has the best result with acid total (2.38), acidity (4.54), sugar total (29.50), viscosity (1.01), color (3.24), flavour (3.08) and taste (3.36) which has grade three.